Can Ropinirole Modulate Reinforcing Subjective Effects of Cocaine in Humans? - Maremmani, Angelo Giovanni Icro; Pacini, Matteo; Rovai, Luca; Rugani, Fabio; Dell'Osso, Liliana; Maremmani, Icro (Frontiers in Psychiatry, 2011)
In this study we evaluated, by means of the “Cocaine Rush Visual Analogue Scale” (CRVAS), the impact of ropinirole on the expected rush induced by cocaine in a group of heroin addicts abusing cocaine; the self-reported reaction to the rush blockade (if any) on cocaine consumption, and the correlations between this self-reported reaction and individual, clinical and therapeutic parameters. Nineteen cocaine abuser heroin-dependent patients entered the study. Their experienced cocaine rush was 61.31±32.1% of the maximum effect previously experienced. Compared with their previous rush intensity 16 patients experienced significantly lower intensity, three the same intensity and none a higher intensity. In particular, two patients experienced a complete blockade of rush and reported a reduced use of cocaine. Fourteen patients experienced a partial blockade of cocaine rush; of these, nine reported they had reduced their use of cocaine. Ropinirole does diminish the subjective intensity of an expected cocaine rush, so interfering with the dynamics of reward, while supporting its possible use in the treatment of cocaine dependence.